2020
DOI: 10.3390/ijerph17238875
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Attitudes towards Immigrants’ Social Rights

Abstract: The migrant population has increased in recent years and, as a result, so has cultural diversity. Universities are incorporating specific modules addressing cultural diversity. However, the native population has negative attitudes towards immigrants, as they believe that immigrants receive more social benefits and abuse healthcare services. Nurses may have these attitudes too, which may affect the way they treat patients. The objective of this study was to determine nursing students’ attitudes towards the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
3
7
0
1
Order By: Relevance
“…We found that some generalizations associated with nationality were linked by health workers to the migrants’ ability to follow instructions, self-care practices and others. These findings are consistent with previous studies on negative beliefs and prejudiced attitudes related to many migrants’ perception of job loss, opportunities and low quality of health care due to unsensitive or poorly culturally pertinent care provided to them [ 42 , 43 , 44 ]. According to Pino’s study, each health team member’s vision can be biased when providing care in the therapeutic relationship and can affect the quality of care [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that some generalizations associated with nationality were linked by health workers to the migrants’ ability to follow instructions, self-care practices and others. These findings are consistent with previous studies on negative beliefs and prejudiced attitudes related to many migrants’ perception of job loss, opportunities and low quality of health care due to unsensitive or poorly culturally pertinent care provided to them [ 42 , 43 , 44 ]. According to Pino’s study, each health team member’s vision can be biased when providing care in the therapeutic relationship and can affect the quality of care [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…Barriers to effective healthcare among international migrants have been widely studied, involving individual aspects such as limited information about the healthcare system in the receiving country, fear of deportation, language, lack of health insurance and educational level. Our study and other similar ones in the international literature suggest the relevance of paying attention to unethical practices in healthcare delivery, such as dehumanized treatment, communication problems, violation of the right to care, discrimination and health services without cultural adaptation to specific diverse communities [ 24 , 26 , 41 , 42 , 43 ]. According to Liberona, the relationship between the health personnel and international migrant users could be intervened by these factors, reproducing scenarios of power asymmetry between both actors [ 21 ].…”
Section: Discussionsupporting
confidence: 65%
“…In the analyses of the nationality variable, it is revealed that the highest level of academic success is indicated in stu-dents of European origin, such as those from Germany, England or Portugal, while the students who obtained lower grades and, therefore, less academic success, were students from China, Japan and South Korea. These results coincide with previous research [122], where it was identified that, depending on the students' nationality, a different degree of integration is achieved in the host country, which significantly influences their academic performance and success.…”
Section: Discussionsupporting
confidence: 91%
“…The third dimension encompasses the defense of one's rights. This dimension consists of students defending their rights to access free education, medical care, the world of work, and, in addition, being recognized by the host society, which must make a greater effort to improve the quality of life of immigrants [122].…”
Section: Theoretical Foundations Of the Instrument Usedmentioning
confidence: 99%
“…Both appreciative 23,24 and discriminative 22,25 relationships are seen between patients and nurses with immigrant backgrounds, and studies show that nursing students display positive attitudes towards immigrant patients. 17,18,26 Nurses' training and socialisation throughout nurse education ought to facilitate patient encounters and accommodation of cultural diversity. This study aims to illuminate how nursing students with an ethnic background other than Danish were socialised into homecare practice during their nurse education in Denmark.…”
Section: Introductionmentioning
confidence: 99%